The Effect of Treaties on Foreign Direct Investment 2009
DOI: 10.1093/acprof:oso/9780195388534.003.0022
|View full text |Cite
|
Sign up to set email alerts
|

It’s All in the Timing: Assessing the Impact of Bilateral Tax Treaties on U.S. FDI Activity

Abstract: Despite substantial evidence that foreign direct investment (FDI) is influenced by taxation, the impact of bilateral tax treaties on FDI is surprisingly unclear. We investigate one possible reason: previous empirical research restricts treaties to have a one-time, discrete effect on FDI. We find this assumption to be rejected in the data on US inbound FDI. Moreover, allowing for anticipatory and lagged effects of treaty formation indicates a more substantial, positive effect on FDI activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Yet the evidence for such an effect is inconclusive. Until 2009, academic studies found a mixed effect of tax treaties on investment flows: positive, neutral or in some instances negative, the latter attributed to tax evading investors likely to be put off by the improved enforcement powers provided by tax treaties (Blonigen & Davies, ; Coupé, Orlova, & Skiba, ; Davies, ; Egger, Larch, Pfaffermayr, et al, ; Louie & Rousslang, ; Millimet & Kumas, ; Neumayer, ). Positive effects on investment were more commonly found for treaties between developed countries than those involving a developing country.…”
Section: The Questionable Case For Tax Treatiesmentioning
confidence: 99%
“…Yet the evidence for such an effect is inconclusive. Until 2009, academic studies found a mixed effect of tax treaties on investment flows: positive, neutral or in some instances negative, the latter attributed to tax evading investors likely to be put off by the improved enforcement powers provided by tax treaties (Blonigen & Davies, ; Coupé, Orlova, & Skiba, ; Davies, ; Egger, Larch, Pfaffermayr, et al, ; Louie & Rousslang, ; Millimet & Kumas, ; Neumayer, ). Positive effects on investment were more commonly found for treaties between developed countries than those involving a developing country.…”
Section: The Questionable Case For Tax Treatiesmentioning
confidence: 99%
“…Yet the evidence for such an effect is inconclusive. Until 2009, academic studies found a mixed effect of tax treaties on investment flows: positive, neutral, or in some instances negative, the latter attributed to tax evading investors likely to be put off by the improved enforcement powers provided by tax treaties (Blonigen and Davies 2004;Coupé et al 2009;Davies 2004;Egger et al 2006;Louie and Rousslang 2008;Millimet and Kumas 2009;Neumayer 2007). Positive effects on investment were more commonly found for treaties between developed countries than those involving a developing country.…”
Section: The Questionable Case For Tax Treatiesmentioning
confidence: 99%
“…Other studies find no or negative effects of DTTs on FDI (e.g. Baker, 2014;Davies et al, 2010;Louie & Rousslang, 2008;Millimet & Kumas, 2008). While some authors like Baker (2014) argue that DTTs simply do not impact FDI decisions, others like Coupé, Orlova and Skiba (2009) or Blonigen et al (2014) attribute inconclusive findings to the conflicting single provisions in the DTTs.…”
Section: Previous Literature On the Effects Of Dtts On Fdi Activitymentioning
confidence: 99%